Transmission Events within Outbreaks of Gastroenteritis Determined through Analysis of Nucleotide Sequences of the P2 Domain of Genogroup II Noroviruses - Xerry, Jacqueline (American Society for Microbiology (ASM), 2008)
Tracking the spread of noroviruses during outbreaks of gastroenteritis is hampered by the lack of sequence diversity in those regions of the genome chosen for virus detection and characterization. Sequence analysis of regions of the genes encoding the RNA-dependent RNA polymerase and the S domain of the capsid does not provide sufficient discrimination between genotypically related strains of different outbreaks. However, analysis of sequences derived from the region encoding the P2 domain showed 100% similarity among strains from the same outbreak and <100% similarity among strains of different outbreaks. The prolonged nature of some hospital outbreaks, links between hospitals, and the introduction of multiple strains of a single genotype associated with an outbreak aboard a cruise ship were determined using this method. This provides a powerful tool for tracking outbreak strains and the subsequent analysis and validation of interventions in a background of multiple introductions of virus strains of the same genotype or genetic cluster.